FACTORS AFFECTING THE QUALITY OF THE GOVERNMENT’S PERFORMANCE ACCOUNTABILITY REPORT WITH GOVERNMENT’S INTERNAL CONTROL SYSTEM AS A MODERATOR VARIABLE AT NORTH LABUHAN BARU DISTRICT - Ulfa, Adrina Harahap (International Journal of Public Budgeting, Accounting and Finance, 2018)
The purpose of the study was to recognize and analyze the influences of performance-based budgeting, resources capacity, and the role of the government's internal oversight apparatus on the quality of government institution performance accountability report at North Labuhan Batu District, simultaneously and partially, with government internal control system as moderator variable. The type of the study was an associative study. The population of the study was financial administration officers, head of the program sub-section and treasurer of North Labuhan Batu District with 120 respondents. The results of the study have proved that simultaneously, performance-based budgeting, resources capacity, and the role of the government' internal Significantly oversight apparatus influences the quality of government institution performance accountability report at North LabuhanBatu District. Partially, resources capacity positively and Significantly influences the quality of government institution performance accountability report at North LabuhanBatu District, but performance-based budgeting and the role of the government's internal oversight apparatus insignificantly influences the quality of government institution performance accountability report at North LabuhanBatu District. Meanwhile government internal control system could not moderate the relationships between performance-based budgeting, resources capacity, and the role of the government's internal oversight apparatus with the quality of Government's Institution Performance Accountability Report at North LabuhanBatu District.